Relationship of Compliance of Personal Protective Equipment Usage and Housekeeping with Near Miss in Nurses - Angela Tesalonika Oktavera; Innaha Ilma Wardaya (Universitas Airlangga, 2023)
Introduction: The hospital is one of workplaces that has a high risk of hazard that can cause near miss. Nurses are people who play an essential role in the medical service environment. Near miss are more common than work accidents and have become a critical point for preventing workplace accidents. This study aimed to analyze the correlation between compliance of PPE usage and housekeeping with near miss in nurses. Methods: This study used a descriptive observational design which was designed in a cross sectional way. Respondents were 53 nurses. The research data presented in the form of frequency distribution, cross tabulation, and correlation analysis. The study's independent variable is compliance of PPE usage and housekeeping, and the dependent variable is near miss. The method of data collecting in this research using a questionnaire for compliance of PPE usage, housekeeping, and near miss. Results: The relationship between housekeeping (rs =-0.259) with near miss among nurses is weak because near miss are primarily due to human error or unsafe behaviour, and housekeeping is a working condition factor that contributes little to the causes of near miss. Medium category correlation between compliance with PPE use (rs = -0.455) with near miss because nurses have an obligation to provide safe nursing actions and protect themselves from potential hazards by using PPE. Conclusion: Compliance of PPE usage and housekeeping that contribute to near miss.